O imaginário de si e sobre a polícia em letras de rap - SOUZA, Luiz Renan Costa de (2021)
This research based on the theory of Pêcheux's Materialist / French Discourse Analysis analyzed the discourse of Hip Hop culture from a corpus composed of Brazilian rap lyrics such as rappers Mc Cid, Emicida, Djonga , MVBIL. The goal is to understand how Rappers project their imaginary about themselves and the police, considering that the rappers selected for analysis are characterized by portraying in their discourse, materialized in lyrics, the conditions of existence of blacks and social layers within suburban and peripheral contexts in Brazil, especially in the cities of São Paulo and Rio de Janeiro. For this, it was also necessary to approach other concepts within the theoretical buildings of Discourse Analysis to select three discourses of three letters of Rap contemplating the imaginary game of subjects of Pêcheux. Thus, we conclude that rap as a genre of social denunciation portrays a game of imaginary in a dialectical way and that evidences historical injustices of the state on the black population.